2008
DOI: 10.1007/s00128-008-9358-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sub-lethal Concentrations of Endosulfan on Phagocytic and Hematological Parameters in Nile Tilapia (Oreochromis niloticus)

Abstract: The effect of endosulfan (6,7,8,9,10,10-hexachloro-1,5,5a,6,9,9a-hexahydro-6,9-methano-2,4,3-benzodioxathiepin-3-oxide), an organochlorine pesticide, was evaluated on phagocytic (phagocytic index and percentage of active cells) and hematological parameters in Nile tilapia. Experimental data showed that an acute exposure to endosulfan (4.0 and 7.0 microg/L) induces a significant decrease in the phagocytic index and the percentage of active cells in peripherical blood of Nile tilapia. However, hemoglobin concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 15 publications
(14 reference statements)
2
12
1
Order By: Relevance
“…This agrees with Girón-Pérez et al (2008) who reported decreased phagocytic activity. Akhtar et al (2010) also reported decreased phagocytic activity, increased A/G ratio, increased cortisol and reduced survival in response to bacterial challenge (17 % less than control).…”
Section: Discussionsupporting
confidence: 93%
“…This agrees with Girón-Pérez et al (2008) who reported decreased phagocytic activity. Akhtar et al (2010) also reported decreased phagocytic activity, increased A/G ratio, increased cortisol and reduced survival in response to bacterial challenge (17 % less than control).…”
Section: Discussionsupporting
confidence: 93%
“…For instance, exposure to sublethal concentrations of this pesticide significantly diminished the phagocytic activity in Nile tilapia (Girón-Pérez et al 2008) and leukocytes count in M. albus (Hii et al 2007). By contrast, we observed a significant increase in WBC of endosulfan exposed P. lineatus, which evidences immunostimulation.…”
Section: Discussioncontrasting
confidence: 64%
“…This in turn might have caused a functional reduction in the vitamin C content in both the tissues thereby exposing them for possible cell injury. The significance of the haematological status of an organism as a biological indicator was established, and various haematological parameters were shown as very sensitive to pesticides toxicity (Luskova 1996;Petri et al 2006;Girón-Pérez et al 2008). The haemoglobin content in our short-term study significantly decreased by 15.5% within 12 h of endosulfan exposure and then further by 25.8% after 24 h of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Endosulfan is highly toxic to fish and shellfish (Petri et al 2006). It can cause severe depression of the fish immune system and consequently increase their susceptibility to infection (Jenkins et al 2003;Girón-Pérez et al 2008). Auffret et al (2006) reported alterations of the immunological parameters (total haemocyte counts, lysosomal stability and phagocytosis) in mussels, Mytilus galloprovincialis, collected from chemically contaminated sites and suggested immunosuppressive conditions in contaminated mussels.…”
mentioning
confidence: 98%